Enhancing Students’ Listening Comprehension through Interactive Multimedia Learning Using Mobile-Based Language Applications - Rosalina, Afni; Fithriani, Rahmah; Pardi (IKIP Siliwangi, 2026)
This study aims to examine the enhancement of students’ listening comprehension through the integration of interactive multimedia learning in English as a Foreign Language (EFL) classrooms. A descriptive qualitative approach was employed, involving 25 secondary school students as participants. Data were collected through observations, interviews, and field notes during the learning activities. The findings reveal that the use of interactive multimedia tools, such as audio-visual materials, animations, and application-based listening tasks, significantly improved student engagement, contextual understanding, and overall listening comprehension. Students demonstrated increased accuracy in identifying main ideas, essential vocabulary, and implicit messages within spoken texts. The learning process also became more dynamic and enjoyable, which contributed to higher learning motivation. Therefore, interactive multimedia learning can be considered an effective instructional strategy for improving students’ listening comprehension in EFL contexts.